Estimating the biological effects of helium, carbon, oxygen, and neon ion beams using 3D silicon microdosimeters. (8th February 2021) - Lee, Sung Hyun; Mizushima, Kota; Kohno, Ryosuke; Iwata, Yoshiyuki; Yonai, Shunsuke; Shirai, Toshiyuki; Pan, Vladimir A; Bolst, David; Tran, Linh T; Rosenfeld, Anatoly B; Suzuki, Masao; Inaniwa, Taku
Abstract: In this study, the survival fraction (SF) and relative biological effectiveness (RBE) of pancreatic cancer cells exposed to spread-out Bragg peak helium, carbon, oxygen, and neon ion beams are estimated from the measured microdosimetric spectra using a microdosimeter and the application of the microdosimetric kinetic (MK) model. To measure the microdosimetric spectra, a 3D mushroom silicon-on-insulator microdosimeter connected to low noise readout electronics (MicroPlus probe) was used. The parameters of the MK model were determined for pancreatic cancer cells such that the calculated SFs reproduced previously reported in vitro SF data. For a cuboid target of 10 × 10 × 6 cm 3, treatment plans of helium, carbon, oxygen, and neon ion beams were designed using in-house treatment planning software (TPS) to achieve a 10% SF of pancreatic cancer cells throughout the target. The physical doses and microdosimetric spectra of the planned fields were measured at different depths in polymethyl methacrylate phantoms. The biological effects, such as SF, RBE, and RBE-weighted dose at different depths along the fields were predicted from the measurements. The predicted SFs at the target region were generally in good agreement with the planned SF from the TPS in most cases.